2013
DOI: 10.1002/alr.21209
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of septal stapler to suture closure in septoplasty: a prospective, randomized trial evaluating the effect on operative time

Abstract: Coaptation of the mucosal flaps in septoplasty with a septal stapler affords a timesaving in the operating room with no difference in operative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…There are only four previous studies on the use of the stapler, one published in Chinese. Sowerby et al (2013) reported that the stapler shortens the closure time with a mean of six minutes, however, we observed no significant time saving (5) . An important difference between our study and Sowerby's is the size, whilst Sowerby's study included 16 patients, our study included 457 patients.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…There are only four previous studies on the use of the stapler, one published in Chinese. Sowerby et al (2013) reported that the stapler shortens the closure time with a mean of six minutes, however, we observed no significant time saving (5) . An important difference between our study and Sowerby's is the size, whilst Sowerby's study included 16 patients, our study included 457 patients.…”
Section: Discussioncontrasting
confidence: 60%
“…An important difference between our study and Sowerby's is the size, whilst Sowerby's study included 16 patients, our study included 457 patients. In Sowerby's study, all operations were performed by the same surgeon, while our material consisted of operations performed by different surgeons (5) . It is possible that we have a selection bias in the group of surgeons using sutures, as it is mostly one very experienced surgeon who uses suturing at our clinic, whereas the stapler was also used by residents, whose operations naturally take a longer time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations